WOMENâ€™S ROLES IN THE MEDIA - Dewi, Ratna Sari (Lentera: Jurnal Ilmiah Kependidikan, 2012)
The purpose of this paper is to investigate the changes of womenâ€Ÿs roles on how women were potrayed in the past and how they are potrayed today, especially in four influential media. Therefore, the question rised in this paper is â€œWhat are the changes of womenâ€Ÿs roles on how women were potrayed in the past and how they are potrayed today, especially in four influential media?â€. This paper shows that there are many proofs showing changes and improvements of womenâ€Ÿs roles on how women were potrayed in the media in the past, and how they are potrayed today, especially in four influential media such as womenâ€Ÿs magazines, television and print media cartoons and fairy tales. When women are depicted in the media, they they are tipically subjected to a greater degree of phisical appearance and more rigid standard of beauty which they are expected to embody. It argued that the central media messages concerning women is that womenâ€Ÿs primary value lies in their physical appearance.